Prodovite, a Novel VMP35 Multi-nutrient Iron-free Supplement, Enhances Cytoprotection Against Anemia in Human Subjects (P06-002-19) - Bagchi, Manashi; Downs, Bernard; Corbier, Jean-Ronel; Kushner, Steve; Aloisio, Ted (Current developments in nutrition, 2019)
Global Burden of Disease 2016 (GBD 2016) reported that Iron Deficiency Anemia (IDA) is the leading cause of anemia, which affect 1.93 billion people worldwide. Anemia is intricately linked to chronic inflammation, chronic kidney disease, gastrointestinal and gynecological malignancies, and autoimmune disorders. Hemorrhagic anemia results in substantial loss of blood which causes significant alterations in all blood parameters, including reduced iron. The other type of non-genetic anemia is chronic anemia syndrome (CAS), which is caused by an increasing anaerobic/acidic environment that forces a defensive expenditure of alkalinizing buffers in hemoglobin, releasing iron and leading to lowering of blood pH. The result is the initiation of a sequel of chronic inflammatory events. Initially, iron cleaved from heme groups is transferred into other vital organs including hepatic tissues, appearing to be IDA. This process results in excessive tissue iron accumulation leading to hemochromatosis, aka ‘iron overload anemia’. Ultimately, tissue iron saturation results in downregulation of tissue storage and a buildup in blood plasma. A novel iron-free safe, nutraceutical supplement, Prodovite VMP35, was developed and assessed in a clinical setting to demonstrate its efficacy in hemoglobin restoration in CAS. A pilot clinical study was conducted to evaluate the safety and efficacy of Prodovite in 38 subjects (men = 10; women = 28; age: 12–82 years). Subjects consumed either placebo or VMP35 (30 ml) and the efficacy was assessed over a period of 0-, 5- or 30 min post-treatment. The safety, rate of absorption and the efficacy of Prodovite was assessed on diverse blood parameters. Changes in peripheral blood smears from 38 subjects were observed using live blood cell imaging (LBCI) with phase contrast microscopy. Adverse events were rigorously monitored. Prodovite exhibited positive changes in the blood including morphological, hematological (including restoration of hemoglobin) and rheological changes following 5 min of administration, which were sustained for at least 30 min. Benefits were also observed in subjects with compromised digestive systems. Overall, iron free Prodovite VMP35, significantly improved blood morphology and restoration of hemoglobin in these subjects. No adverse events were reported. The Study was funded by Victory Nutrition Inc., Lederach, PA.